Pengaruh Gaya Kepemimpinan, Motivasi Kerja, Komitmen Organisasional, Budaya Organisasi dan Kepuasan Kerja Terhadap Kinerja Karyawan (Studi Empiris pada Bank Syariah di Surakarta) - Daryanti, Susi, Dr. Fatchan Achyani, S.E, M.Si (2016)
This study aimed to examine the effect of leadership style, work motivation, organizational commitment, organizational culture, and job satisfaction on employee performance. Employee performance is the success rate of employees in carrying out their duties and responsibilities. Improving employee performance will bring progress for the organization to be able to survive in a competition.The population in this study were all employees who work in islamic banks in Surakarta. The sampling technique in the study used traditional convenience sampling, and the selection based on simplicity, so that researchers have the freedom to select a sample. Methods of data collection was done by using a questionnaire survey. The data analysis used in this research was multiple linear regression analysis. The results of this research show that leadership style, work motivation, organizational commitment, organizational culture, and job satisfactionhave a positive significanton employee performance.